2016
DOI: 10.1111/jfb.12884
|View full text |Cite
|
Sign up to set email alerts
|

Comparative movements of four large fish species in a lowland river

Abstract: A multi-year radio-telemetry data set was used to comparatively examine the concurrent movements of the adults of three large-bodied Australian native freshwater fishes (Murray cod Maccullochella peelii, trout cod Maccullochella macquariensis and golden perch Macquaria ambigua) and the introduced carp Cyprinus carpio. The study was conducted over a reach scale in the regulated Murray River in south-eastern Australia. Differences were identified in the movements among these species. The predominant behaviour wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 70 publications
5
43
0
1
Order By: Relevance
“…We found that both M. peelii and M. ambigua in a weir pool exhibit strong site fidelity, and that M. ambigua used woody debris, similar to observations on riverine populations (Crook, ; Crook et al ., ; Koehn & Nicol, ). In comparison, some behaviours differed from those previously observed, especially the absence of longer‐distance (tens to hundreds of kilometres) movements and a lack of habitat associations for M. peelii .…”
Section: Discussionmentioning
confidence: 99%
“…We found that both M. peelii and M. ambigua in a weir pool exhibit strong site fidelity, and that M. ambigua used woody debris, similar to observations on riverine populations (Crook, ; Crook et al ., ; Koehn & Nicol, ). In comparison, some behaviours differed from those previously observed, especially the absence of longer‐distance (tens to hundreds of kilometres) movements and a lack of habitat associations for M. peelii .…”
Section: Discussionmentioning
confidence: 99%
“…Maccullochella peelii are currently listed as critically endangered (Wager, 1996), and T. tandanus are listed as an endangered population in the MDB in NSW (NSW Fisheries Management Act 1994). Such movements may also coincide with the species' breeding activities (Koehn et al, 2009;Koehn & Nicol, 2016). Such movements may also coincide with the species' breeding activities (Koehn et al, 2009;Koehn & Nicol, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…These two species have undergone dramatic range contractions and declines in abundance due to the introduction of Common carp (Cyprinus carpio), cold water pollution, altered flow regimes and the loss of suitable habitat (Barrett, 2004;Koehn, Lintermans, & Copeland, 2014). Both species show relatively restricted movements over much of their life, occupying well-defined home ranges (Koehn et al, 2009;Koehn & Nicol, 2016;Koster et al, 2015), although both may also undertake occasional long-distance movements during periods of high flow (Koster et al, 2015;Marshall et al, 2016;Reynolds, 1983). Both species show relatively restricted movements over much of their life, occupying well-defined home ranges (Koehn et al, 2009;Koehn & Nicol, 2016;Koster et al, 2015), although both may also undertake occasional long-distance movements during periods of high flow (Koster et al, 2015;Marshall et al, 2016;Reynolds, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…1) when the Trout Cod stocking program commenced in 1988 (Lintermans, 2002). Murray Cod are known to undertake upstream spawning migrations (Koehn et al, 2009) but adult Trout Cod are less mobile, at least in lowland rivers, than Murray Cod (Koehn & Nicol, 2016). The major stocking site for Trout Cod (99,500 fish from 1996 to 2005) was at Angle Crossing immediately upstream of Gigerline Gorge and so the presence of a migration barrier may result in aggregations of reproductively ripe Murray Cod mixing with downstream displaced trout cod below the barrier, further enhancing the chance of hybridization.…”
Section: Discussionmentioning
confidence: 99%